Constructing a Software Tool to Optimize Performance by Coupling Detection - Tawfeeq, Tawfeeq (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
Coupling relations reflect the interdependencies of software modules and can be used to assess a program's quality— Lower the coupling value will be, the higher the quality of the software will be. Coupling measures are crucial for determining the quality of object-oriented software, from design up to maintenance. Inside software engineering, quality attributes are realized non-functional requirements utilized to assess whether the software is of good quality or not, One of the quality attributes is Performance, which means the system can respond to various actions in a given time or how fast does it respond or execute. To calculate the total amount of time a program will require to run until completion use Time Complexity. In this paper a Computer Aided Software Engineering Tool has been constructed which is called CDPI (Coupling Detection to Performance Improvement). It parse a software source code to extract information about its structure, components, and relationships that connect its parts. That leads to improving the software readability, understandability and for detects coupling among classes of Java software.The CDPI tool detects coupling in software source code and Show it in table to the software engineer, To start the process of decoupling by the software engineer for the candidate coupling. The CDPI tool was tested by inputting software written in OOP by Java language. The CDPI Tool were evaluated by calculating the Time Complexity before and after decoupling. Results, source code after the decoupling is executed faster than before decoupling to produce the required output, which is an indication of Optimize Runtime Performance of the program.